Composition modulation in one-dimensional and two-dimensional chalcogenide semiconductor nanostructures. (12th September 2018) - Li, Honglai; Wang, Xiao; Zhu, Xiaoli; Duan, Xiangfeng; Pan, Anlian
Abstract : This article reviews our successful realization of the composition modulated single chalcogenide semiconductor nanostructures. Abstract : Low dimensional heterostructures have potential applications in information, sensing, and energy-related technologies. In order to obtain high-quality low dimensional heterostructures, an essential method is tuning chemical composition in a single nanostructure to obtain two or multiple components with well-matched electronic band structures. Here, we present a tutorial review of a unique chemical vapor growth approach with in situ switchable solid chemical sources that can build composition-modulated chalcogenide heterostructures in one-dimensional nanowires, quasi one-dimensional nanobelts and two-dimensional atomic layered nanosheets in a controlled manner. This approach has generated a large variety of heterostructures that not only exhibit gradient distribution in chemical composition, but also show sharp interfaces. Diverse integrated photonic and optoelectronic devices are enabled by the composition-modulated heterostructures based on chalcogenides or other material systems.